6+y
Since increased (key word) means addition.
Solve the equation by substitution method.
To get b-2-3b=4. Then you substitute b into simplest to get, b=-3. Repeat the same process with a to get, a=-5. So your answer would be (-5, -3)
a. 3^4 which is equal to (3^-3)(3^7)
The answer to this is D or at least that's what I got
Answer:
The solution is (x,y)=(-4,-1)
Step-by-step explanation: Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.